PENERAPAN METODE PROTOTYPE DAN FORWARD CHAINING UNTUK SISTEM PENDAFTARAN DAN PEMBAYARAN PESERTA DIDIK RUMAH QUR'AN BERBASIS WEBSITE - Nur Aida Azzuhra; Mansur Mansur (STMIK KAPUTAMA, 2025)
Rumah Quran and Rumah Yatim Aisyah are non-formal educational institutions focused on Quranic learning. The processes of student registration and tuition payment are carried out manually, which poses risks such as data entry inaccuracies, delays in reporting, and inefficiencies in administrative management. This study aims to develop a web-based application using the Laravel framework and MySQL database through a prototype development method. The system automates the registration and tuition payment processes, particularly for students from low-income families. A decision support system (DSS) based on the forward chaining method is used to determine the appropriate tuition fee by considering guardian income, number of dependents, and monthly expenses. The test results show that the system improves operational efficiency, reduces recording errors, and accelerates the generation of monthly financial reports. With this system, the management of student data and tuition payments becomes more transparent, accurate, and objective, supporting better financial decision-making within the institution.